Collegiate living environments: a predictor of binge drinking, negative consequences, and risk-reducing behaviors. - Boyd CJ; McCabe SE; d'Arcy H (Journal of Addictions Nursing, 2004)
The purpose of this study was to examine the living environments of undergraduate college students as a predictor of 3 behaviors: binge drinking, its adverse consequences, and the risk-reducing activities used to mitigate binge drinking consequences. In March of 1999, we conducted a cross-sectional, Web-based survey using a random sample of 2,041 undergraduate students attending a large, public university in the Midwest. The students self-administered the Student Life Survey, a questionnaire that was first developed by researchers at the University of Michigan in 1993 as a paper and pencil survey but was adapted in 1999 for the Web. The sample was recruited via E-mail, and students completed the survey from their computer terminals. A 68% response rate was obtained. In our analyses, we controlled for pre-college drinking behavior and found that students' living arrangements remained highly predictive of binge drinking; we found that Substance-Free Housing confers protective effects for both negative consequences and preventative behaviors.